Ethical-Moral Rights and Conflict Management - Cardoso de Oliveira, Luís Roberto (Anuário Antropológico, 2023)
The text discusses the place of ethical-moral rights in processes of conflict management and in demands for citizenship rights from a comparative perspective. Drawing on cases brought to small claims courts in the US, demands for recognition in Quebec, and patterns of inequality of treatment in Brazil, the text reflects upon the importance of these rights and the respective difficulties to redress them adequately.